Improvement of CH election in three-level heterogeneous WSN - Jong-Yong Lee; Daesung Lee (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A Wireless Sensor Network is a wirelessly configured Sensor Node with limited power such as a battery. There are many Wireless Sensor Network Protocols to increase energy efficiency, among which LEACH Protocol and SEP are typical. The LEACH Protocol is mainly used for homogeneous sensor networks with the same initial energy, and SEP is used for heterogeneous sensor networks with different initial energies. In the case of SEP-E, another heterogeneous sensor with different initial energy is added. SEP and SEP-E provide a higher probability of Cluster Head election for node types with more energy than Normal Nodes. Since the current residual energy of the node is not confirmed, even if the energy is low, the Cluster Head may be elected because of the node type. In this paper, considering the residual energy of a node when a Cluster Head is elected, we increase the probability of electing a Cluster Head with more residual energy. Cluster Head consumes a lot of energy. A node with a lot of residual energy is elected as a Cluster Head, so the network lifetime can be used for a long time.